Taguchi Approach to Defect Analysis on Electric Motor Conversion at PT. Electric Vehicle Trimotorindo - Siregar, Hendri Simon; Sutopo, Prihantoro Syahdu (Jurnal Indonesia Sosial Sains, 2024)
Maintaining product quality can reduce the risk of defective products. The survival of a company is heavily reliant on product quality. In order to improve performance and reduce defects in the product process, PT. Electric Vehicle Trimotorindo employs the Taguchi approach in conjunction with the QC system. The goal of this research is to determine the product process of PT. Trimotorindo Electric Vehicle, identify the highest rejection rate, evaluate process capability, and propose improvements using the Kaizen system. This study uses the Taguchi system to optimize the product process of PT. Trimotorindo Electric Vehicles. After collecting data from the taguchi system, it can be concluded that the highest position of blights in a conversion process is in the electric current string.